2017
DOI: 10.1021/acs.biochem.7b00015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Doxorubicin, Cisplatin, and Tamoxifen on the Metabolic Profile of Human Breast Cancer MCF-7 Cells As Determined by 1H High-Resolution Magic Angle Spinning Nuclear Magnetic Resonance

Abstract: Doxorubicin (Doxo), cisplatin (Cis), and tamoxifen (Tamo) are part of many chemotherapeutic regimens. However, there have been limited studies of the way metabolism in breast cancer is affected by chemotherapy. We studied, through H high-resolution magic angle spinning nuclear magnetic resonance (HR-MAS NMR) spectroscopy, the metabolic profile of human breast cancer MCF-7 control (Con) cells as well as MCF-7 cells treated with Tamo, Cis, and Doxo.H HR-MAS NMR single-pulse spectra evidenced signals from the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…All spectra displayed in Fig. 1 showed strong, broad peaks overlapped with sharp, weak ones, the latter being assigned to water-soluble metabolites similar to those observed in MCF-7 cells [11]. The broad, strong peaks at 0.9 [1] and 1.3 ppm [2] have been assigned to methyl and methylene groups of fatty acids and proteins, respectively.…”
Section: Spectra Assignmentssupporting
confidence: 56%
See 4 more Smart Citations
“…All spectra displayed in Fig. 1 showed strong, broad peaks overlapped with sharp, weak ones, the latter being assigned to water-soluble metabolites similar to those observed in MCF-7 cells [11]. The broad, strong peaks at 0.9 [1] and 1.3 ppm [2] have been assigned to methyl and methylene groups of fatty acids and proteins, respectively.…”
Section: Spectra Assignmentssupporting
confidence: 56%
“…We have previously studied the influence of chemotherapy on metabolic profile of the estrogen receptor-positive human breast cancer cell line MCF-7 using 1 H high-resolution magic angle spinning (HR-MAS) NMR spectroscopy [11]. This technique confirmed that doxorubicin, cisplatin, and tamoxifen had strong effects on the metabolic profile of MCF-7 cells [11].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations